Quantification and characterization of plastic waste generated in the municipality of Puerto Carreño, Vichada. - Zapata Zuñiga, Maria Camila
The municipality of Puerto Carreño, capital of the department of Vichada, does not have a characterization of plastic waste produced by its inhabitants, these being a major problem at the municipal level, due to its inadequate management, as well as very low utilization and separation at the source by users, so it is necessary to initiate actions to include them within the circular economy. In this sense, and in order to have basic information for decision-making, the plastic waste produced was quantified and characterized, according to its typology, taking a sample with a confidence level of 80% and error of 15%, which showed that the 6,590 users of the toilet service in the urban area of the municipality, generate approximately 10,473 kg of plastic waste, among which the most produced is Polyethylene Terephthalate (PET), and the least produced, Polyvinyl Chloride (PVC).